Black phosphorus crystal change material, modification method and anti-tumor application thereof
By combining black phosphorus with transition metal ions to form TMP QDs, the low photothermal conversion performance and structural stability of black phosphorus under NIR-II light is solved, and efficient tumor targeted delivery and complete removal are achieved, avoiding cancer relapse.
Patent Information
- Application Number
- CN202411285998.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
AI Technical Summary
The low photothermal conversion performance of black phosphorus in the NIR-II biological window leads to its limitation in biomedical applications and insufficient structural stability in complex internal environments, resulting in tumor cells not being completely killed, leading to cancer recurrence .
The black phosphorus crystals are combined with transition metal ions through topological chemistry to form transition metal phosphide quantum dots (TMP QDs) to improve their photothermal conversion performance under NIR-II light, and to develop an integrated multifunctional nano platform for Targeted delivery to achieve complete tumor removal.
TMP QDs significantly improve the photothermal conversion efficiency and stability under NIR-II light, achieve targeted enrichment and complete clearance of tumors, and avoid cancer recurrence.
Smart Images

Figure CN119306190A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a black phosphorus crystal-transformed anti-tumor composite material, belonging to the technical field of hospital materials. Background Art
[0002] Among various two-dimensional (2D) materials, black phosphorus (BP) has been widely used in photothermal therapy (PTT) due to its wide light absorption, good biosafety and biodegradability, and large specific surface area. However, after reviewing previous reports on PTT mediated by BP nanomaterials, we found that the clinical application of BP as photothermal agents (PTAs) still faces some obstacles. First, despite the efforts to improve the photothermal conversion efficiency (PCE) through surface modification, BP-based nanoplatforms are still sensitive to near-infrared light (NIR-I, 750-1000 nm), usually 808 nm laser. The low tissue penetration depth, maximum permissible exposure (MPE), and spatial resolution of NIR-I light severely limit the biomedical application of BP. Second, due to the uneven distribution and low accumulation of BP PTAs in tumor cells, tumors cannot be completely ablated. Third, the environmental instability of BP before reaching the tumor site may adversely affect its photothermal effect, hindering its practical application. Therefore, it is of great significance to transform BP into NIR-II (1000-1500 nm) activated PTAs with high PCE through structural reconstruction and further develop an integrated multifunctional nanoplatform to achieve targeted delivery of BP and complete elimination of tumors.
[0003] Recent studies have reported the conversion of BP nanomaterials into PTAs responsive to NIR-II light. For example, carbon dots responsive to NIR-I light (NIR-II-CD) were electrostatically adsorbed onto the surface of BP nanosheets to form NIR-II-CD / BP hybrids [ ACS Appl. Mater. Interfaces 2019, 11 , 44949]. Recently, the fullerene covalent passivation method was used to convert C 60 Covalently grafted onto BP nanosheets, the resulting BP-ester-C60 was applied in NIR-II PTT [ ACS Appl. Mater. Interfaces 2023, 15, 20686.]. Although these BP mixtures exhibit considerable NIR-II PTT effects, the structural stability of physical or chemical mixing strategies is a concern in the complex in vivo environment. Metal phosphides with low-energy electrons and corresponding NIR-Ⅱ absorption capabilities may provide a feasible strategy for the synthesis of NIR-II responsive BP nanomaterials. However, there are no reports on the conversion of BP nanomaterials for NIR-II PTT via lattice reconstruction.
[0004] Single-mode PTT usually leads to cancer recurrence because tumor cells are not completely killed. To solve this problem, people have developed a variety of combined treatment strategies, such as PTT combined with chemotherapy, chemodynamic therapy (CDT), photodynamic therapy (PDT), radiotherapy, gas therapy, gene therapy, immunotherapy, etc., to improve the therapeutic effect of PTT. Among them, chemotherapy combined with PTT is one of the most widely used and irreplaceable treatment methods, and has great potential for clinical transformation.
[0005] However, the above technical solution still has the following problems 1. The low photothermal conversion performance of black phosphorus (BP) in the NIR-II biological window (1000-1500 nm) limits the application of BP as a photothermal agent in biomedicine.
[0006] 2. In the complex in vivo environment, the structural stability of physical or chemical hybrid modified BP strategies is insufficient.
[0007] 3. Single-mode PTT usually leads to cancer recurrence because tumor cells are not completely killed.
[0008] 4. The distribution of BP photothermal agent in tumor cells is uneven and the accumulation is low. Summary of the invention
[0009] The purpose of the present invention is to transform BP into NIR-II activated PTAs with high PCE through crystal transformation modification and further develop an integrated multifunctional nanoplatform to achieve targeted delivery of BP and complete elimination of tumors.
[0010] Based on this, the main technical problems solved by this application include: (1) The photothermal conversion performance of black phosphorus (BP) in the NIR-II biological window (1000-1500 nm) is low, which limits the application of BP as a photothermal agent in biomedicine.
[0011] (2) Single-mode PTT usually leads to cancer recurrence because tumor cells are not completely killed.
[0012] In view of the above problems, the present invention provides a black phosphorus crystal transformation material, wherein the black phosphorus crystal transformation material is a transition metal phosphide quantum dot formed by black phosphorus crystals and transition metal ions, and the average particle size of the composite material is 2.0-10.0 nm. BP is converted into NIR-II activated PTAs with high PCE through crystal transformation modification.
[0013] The transition metal ions include Ni 2+ 、Co 2+ , Fe 3+ , Cu 2+ One or more of .
[0014] In some embodiments, the transition metal phosphide quantum dots (TMP QDs) include any one of nickel phosphide quantum dots Ni2P QDs, cobalt phosphide quantum dots Ni2P QDs, iron phosphide quantum dots Ni2P QDs, and copper phosphide quantum dots Ni2P QDs; The black phosphorus crystal transformation material is Ni2P QDs, and X-ray powder diffraction has characteristic peaks at 2-Theta of about 40.8°, 44.6°, 47.3°, and 54.2°; The black phosphorus crystal transformation material is CoP QDs, and X-ray powder diffraction has characteristic peaks at 2-Theta of about 31.6°, 46.2°, and 58.1°; The black phosphorus crystal transformation material is Fe3P QDs, and X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 41.4°, 41.8°, 42.2°, 43.1°, and 45.3°; The black phosphorus crystal transformation material is Cu3P QDs, and X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 36.0°, 39.1°, 41.6°, 45.2°, 46.3°, and 47.4°; The average particle size of the composite material is 2.0-10.0 nm.
[0015] To achieve this purpose, the present invention reconstructs the lattice of BPQDs by topological chemistry. The specific preparation method is to perform a solvothermal reaction between a transition metal salt and black phosphorus crystal BPQDs in a strong alkaline environment to obtain transition metal phosphide quantum dots (TMP QDs), which are black phosphorus crystal transformation materials.
[0016] The BPQDs are prepared by ultrasonic exfoliation of black phosphorus crystals, refer to patent CN106190120A.
[0017] The particle size of the BPQDs is between 2 and 6 nm.
[0018] The strongly alkaline environment refers to a pH of 9-13.
[0019] The strong base used in the strong alkaline environment includes any one of potassium methoxide, sodium methoxide, potassium ethoxide and sodium ethoxide.
[0020] The transition metal salt is a transition metal ion including Ni 2+ 、Co 2+ , Fe 3+ , Cu 2+ The salt includes one of chloride, nitrate, phosphate and sulfate.
[0021] The hydrothermal reaction temperature is 140-180° C., the reaction time is 4-8 hours, and the hydrothermal reaction process is an oxygen-free environment.
[0022] The solvent is one or more of N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF).
[0023] With respect to the above technical scheme, the TMP QDs obtained in the present invention include one of Ni2P QDs, CoP QDs, Fe3P QDs, and Cu3P QDs.
[0024] The structure and morphology of the TMP QDs material obtained in the present invention are characterized by tests such as X-ray diffraction (XRD), transmission electron microscopy (TEM), dynamic light scattering (DLS), energy dispersive spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS).
[0025] XRD, EDS, XPS and other analysis results show that the TMP QDs were successfully prepared.
[0026] TEM, DLS and other results show that the particle size of the TMP QDs is 2-10 nm, and more preferably between 2 and 5 nm.
[0027] Another object of the present invention is to provide a photothermal effect material, including the black phosphorus crystal-changing material or the black phosphorus crystal-changing material prepared by the method described.
[0028] The black phosphorus crystal-changing material is used in materials that achieve photothermal conversion performance under a light source of 1000-1500nm.
[0029] Given the above-mentioned photothermal effect materials, the present invention provides a NIR-II photothermal conversion performance test method for BPQDs and TMP QDs, specifically including absorption spectrum test, extinction coefficient test, photothermal heating curve test, cycle test, and photothermal conversion efficiency test.
[0030] The present invention compares the absorption of BPQDs and Ni2P QDs in the NIR-II window and measures their UV-visible-NIR absorption spectra at the same concentration.
[0031] The absorption spectrum shows that the absorption rate of BPQDs at 1064 nm is very low, resulting in poor photothermal performance of BPQDs in the NIR-II window. Due to the presence of low-energy electrons, the introduction of transition metal ions may enhance the absorption of nanomaterials in the NIR-II band. The absorption of TMP QDs in the NIR-II region is concentration-dependent.
[0032] According to the Lambert–Beer law (A = εbc, where ε is the extinction coefficient), the absorption intensity at 1064 nm is linearly related to the concentration in the NIR-II region, and the calculated value of ε for TMP QDs is 8.2–9.8 L g −1 cm −1 , relative to BPQDs’ 7.0 L g −1 cm −1 There has been some improvement.
[0033] The TMP QDs aqueous solution was exposed to a power density of 1.0 W / cm 2 The photothermal conversion performance of TMP QDs with different concentrations (0, 25, 50, 100 ppm) was tested using a NIR-II laser (1064 nm). 1 ml of TMP QDs aqueous dispersion was placed in a quartz cuvette with a diameter of 1 cm and irradiated with a fiber-coupled continuous irradiation semiconductor diode laser at a wavelength of 1064 nm and a power density of 1 W / cm 2 The laser spot was adjusted to cover the entire surface of the sample, and infrared thermal imaging was performed to record the temperature changes using a camera.
[0034] When the concentration of TMP QDs reaches 100 ppm, the temperature can be increased to 48.2-53.4 o C, which is high enough to kill tumor cells and remove them at the same time. However, 100 ppm BPQDs can only be heated to 40.9 o C.
[0035] TMP QDs exhibit a laser power-dependent photothermal effect (0.3, 0.5, 0.75, 1.0 W / cm 2 ), as the laser power density increases, the temperature rise will also increase.
[0036] To further evaluate the photothermal stability of TMP QDs in the NIR-II window, 1064 nm laser irradiation was performed for 2 minutes (laser on), followed by natural cooling to room temperature (laser off), and five on / off cycles were performed and the cyclic temperature changes were recorded. No obvious degradation of the photothermal performance was observed during the cycle, confirming the photothermal stability of TMP QDs.
[0037] The NIR-II photothermal conversion efficiency of TMP QDs can be obtained based on the heat transfer time constant and the maximum steady-state temperature. ) is 43.5-48.6%, which is much higher than the photothermal conversion efficiency of BPQDs.
[0038] Based on the above-mentioned photothermal effect material, the present invention provides an application of a material containing transition metal phosphide quantum dots in the preparation of targeted delivery drugs to achieve anti-tumor drugs, and the transition metal phosphide quantum dots include the black phosphorus crystal change material or the black phosphorus crystal change material prepared by the method described.
[0039] Based on the above-mentioned photothermal effect material, the present invention provides an application of a material containing transition metal phosphide quantum dots in the preparation of a drug for targeted delivery of drugs to achieve tumor clearance, and the transition metal phosphide quantum dots include the black phosphorus crystal change material or the black phosphorus crystal change material prepared by the method described.
[0040] Another object of the present invention is to provide a liposome nano-platform, comprising liposomes and black phosphorus crystal transformation materials.
[0041] An integrated multifunctional nanoplatform was developed to achieve targeted delivery of quantum dots and complete tumor clearance.
[0042] The liposome nano-platform is prepared by dissolving dipalmitoylphosphatidylcholine, cholesterol, cRGD and black phosphorus crystal material in a chloroform solvent, drying under reduced pressure by a rotary evaporator to generate a lipid membrane; hydrating the lipid membrane with a PBS solution, sonicating and centrifuging the hydrated lipid membrane, and retaining the supernatant to obtain the liposome nano-platform.
[0043] The molar ratios among DPPC, cholesterol, cRGD, and TMP QDs were (1:0.5-0.7:0.4-0.7:0.2-0.4), and the probe sonication time was 10-20 min (20-40 s on, 10 s off in each cycle).
[0044] Given the photothermal effect material proposed by the photothermal effect of TMP QDs mentioned above, the liposome nano-platform described in the present invention also has a photothermal effect. The liposome nano-platform is used as a photothermal effect material to prepare targeted delivery drugs to achieve anti-tumor drugs; it also has an application in preparing targeted delivery drugs to achieve tumor removal drugs.
[0045] Under NIR-II laser irradiation, the liposomes were released due to the photothermal effect of TMP QDs, and the release rate and amount of the drug were controlled by the laser intensity and exposure time.
[0046] Based on this, the present invention uses liposomes to encapsulate and coat TMP QDs and anti-tumor drugs to form a liposome nanoplatform, wherein the liposome platform is a liposome nanosphere composed of a hydrophobic lipid bilayer membrane and a hydrophilic inner layer, which is used to encapsulate TMP QDs and anti-tumor drugs into the lipid bilayer and inner layer of the liposome, respectively, to form anti-tumor drugs.
[0047] In some embodiments, a typical tumor targeting molecule DSPE-PEG200-cRGD (cRGD) was further modified onto the liposome surface to enhance the targeting of the nanoplatform.
[0048] The present invention also provides an anti-tumor drug, which comprises an anti-tumor drug active ingredient and a black phosphorus crystal transformation material.
[0049] The anti-tumor drug is a composite drug formed by encapsulating the active ingredients of the anti-tumor drug and the black phosphorus crystal transformation material into the lipid double layer and the inner layer of the liposome.
[0050] In some embodiments, the anti-tumor drug is prepared by dispersing the liposome nanoplatform in a citric acid / sodium citrate dispersion at pH 3.0-5.0, further adjusting the pH to 6.0-8.0 by adding citric acid, and then adding the active ingredient of the anti-tumor drug to achieve the encapsulation of the anti-tumor drug, thereby obtaining the anti-tumor drug, which is a liposome-TMP QDs composite material (containing the anti-tumor drug).
[0051] The encapsulation efficiency of antitumor drugs was measured by fluorescence spectrophotometry (λ ex =505 nm, λ em =559 nm) test. Calculated according to the following equation: Coverage = (I max -I0) / I max *100%, where I0 is the fluorescence intensity of the liposome suspension at the initial stage, I max is the fluorescence intensity after adding 0.5% Triton X-100.
[0052] The coverage rate of the anti-tumor drug in the present invention is 94%-98%.
[0053] The liposome-TMP QDs composite material (containing anti-tumor drugs) obtained by the present invention is characterized in morphology by tests such as TEM and DLS.
[0054] The diameter of the liposome-TMP QDs composite material (containing anti-tumor drugs) obtained by the present invention is 70-140 nm.
[0055] The liposome-TMP QDs composite material (containing anti-tumor drugs) obtained by the present invention rapidly releases the anti-tumor drugs and separates from the liposomes under light irradiation. The release curve shows a sudden release within the first 5 minutes, and the release efficiency is between 30.6% and 48.8%.
[0056] The active ingredients of the anti-tumor drug include one or more of alkylating drugs, platinum drugs, and anthracycline drugs; The alkylating agent drugs include nitrogen mustard or cyclophosphamide; the platinum drugs include cisplatin or oxaliplatin; and the anthracycline drugs include doxorubicin.
[0057] The anti-tumor drug (liposome-TMP QDs composite material (containing the anti-tumor drug)) can be used in preparing drugs for treating tumors by realizing rapid release of the anti-tumor drug under light irradiation and separation from the liposome.
[0058] The light irradiation is irradiation under a light source of 1000-1500 nm; the dosage of the anti-tumor drug is 25-100 ppm.
[0059] A light-switchable anti-tumor drug (liposome-TMP QDs composite material (containing anti-tumor drug)), comprising the anti-tumor drug. Specifically, when the NIR-II light is turned off, the release of the anti-tumor drug stops, and when the NIR-II light is restored, the release of the anti-tumor drug restarts.
[0060] Under the physiological environment of the present invention, the liposome composite material (anti-tumor drug) obtained by the present invention remains stable after being placed for 3 weeks (exceeding the treatment course).
[0061] The cells of tumor diseases include MCF-7 cells, Hela cells, 4T1 cells, or MIA PaCa-2 cells.
[0062] Biocompatibility is essential for nanomaterials in drug delivery systems. After adding 100 ppm of liposome-TMP QDs composite material (containing anti-tumor drugs) to the present invention and culturing for 48 hours, the survival rate of MCF-7 cells is close to 100%, indicating that the liposome composite material has relatively low cytotoxicity and good biocompatibility.
[0063] The technical solution of the present invention takes MCF-7 cells as an example to detect the uptake of liposome composite materials in MCF-7 cells. The liposome-TMP QDs composite material (containing anti-tumor drugs) is labeled with Cy5.5 and then observed with a confocal fluorescence microscope. After the liposome composite material is incubated for 2 hours in the cell, effective and rapid cell uptake is achieved.
[0064] The present invention provides an in vitro photothermal combined chemotherapy anti-tumor effect of a liposome-TMP QDs composite material (containing an anti-tumor drug), which is evaluated in real time by cell counting kit-8 (CCK-8) testing and live (calcein AM, green fluorescence) / dead (PI, red fluorescence) cell staining.
[0065] The cell survival rates of the chemotherapy group, photothermal group, and photothermal-chemotherapy group were 50-61%, 40-51%, and 0-3%, respectively.
[0066] The present invention provides the in vivo tumor targeting effect of a liposome-TMP QDs composite material (containing an anti-tumor drug). Cy5.5-labeled TMP QDs material and the liposome composite material are intravenously injected into tumor mice. In vivo fluorescence imaging is observed.
[0067] Unlike the fluorescence signal of free TMP QDs distributed throughout the mouse, the fluorescence signal of liposome-TMP QDs composites (containing anti-tumor drugs) was targeted and accumulated at the tumor site.
[0068] The temperature of mouse tumors treated with liposome-TMP QDs composites (containing anti-tumor drugs) rose rapidly and steadily to 58.5-63.4°C after 10 min of 1064 nm laser irradiation.
[0069] The present invention provides the anti-tumor effect of photothermal combined with chemotherapy in vivo of liposome-TMP QDs composite materials (containing anti-tumor drugs). The anti-tumor effect of mice treated with single photothermal treatment or chemotherapy was improved, but the tumor could not be completely ablated and would recur. The tumor of mice treated with photothermal-chemotherapy combination was completely ablated.
[0070] During the treatment, the mice's weight did not change and their organs were not damaged, indicating the biosafety of this treatment.
[0071] Compared with other groups, the tumor tissues of mice in the photothermal chemotherapy group showed more severe nuclear atrophy and cell apoptosis, indicating that this treatment has excellent clinical application prospects.
[0072] The technical solution of the present invention has the following beneficial effects: 1. The photothermal conversion performance of black phosphorus (BP) in the NIR-II biological window (1000-1500 nm) is low, which limits the application of BP as a photothermal agent in biomedicine. In the complex in vivo environment, the structural stability of the physical or chemical mixed modification BP strategy is insufficient. In addition, the distribution of BP photothermal agents in tumor cells is uneven and the accumulation is low. The present invention uses black phosphorus quantum dots (BPQDs) as templates and adopts a topological chemical method to achieve lattice reconstruction of BPQDs. On this basis, ultrasmall transition metal phosphide quantum dots (TMP QDs) are synthesized. Compared with BPQDs, the absorption and photothermal conversion efficiency of TMP QDs at 1064 nm are significantly improved. Compared with physical or chemical mixed modification strategies, the lattice reconstruction modification has good structural stability.
[0073] 2. Single-mode PTT usually leads to cancer recurrence because tumor cells are not completely killed. The present invention further develops an integrated multifunctional nanoplatform to achieve targeted delivery of BP and complete elimination of tumors. Targeted enrichment of tumors and photothermal combined chemotherapy are simultaneously achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 : Transmission electron microscopy images of Ni2P QDs, CoP QDs, Fe3P QDs, and Cu3P QDs.
[0075] Figure 2 : XRD patterns of Ni2P QDs, CoP QDs, Fe3P QDs, and Cu3P QDs.
[0076] Figure 3 : XPS pattern of Cu3P QDs.
[0077] Figure 4 : EDS spectra of Ni2P QDs and BPQDs.
[0078] Figure 5 : Absorption spectra of Fe3P QDs with different concentrations.
[0079] Figure 6 : TEM image of liposome material of Example 8.
[0080] Figure 7 : DLS image of liposome material in Example 9.
[0081] Figure 8 : Cytotoxicity of liposome composites at different concentrations.
[0082] Fig. 9 :Intracellular uptake of Ni2P QDs and Ni2P@Lipo Fig.10 : The therapeutic effects of 4 groups of cells.
[0083] Fig.11 :In vivo fluorescence distribution of Ni2P QDs and Ni2P@Lipo Fig.12 : Tumor ablation effects in 4 groups.
[0084] Fig.13 :Tumor tissue imaging of 4 groups of treated mice DETAILED DESCRIPTION Example 1 Preparation of BPQDs BPQDs are prepared by ultrasonic exfoliation of black phosphorus crystals, referring to patent CN106190120A, and Example 1 is used as the case in this case.
[0085] Example 2 Preparation of Ni2P QDs In the glove box, take 20 ml of the BPQDs supernatant after centrifugation at 9000 rpm, add 10 mg of potassium methoxide, pH 10.2, 200 mg NiCl2⋅6H2O, and stir to obtain a uniform dispersion. The dispersion was transferred to a polytetrafluoroethylene (25 ml) reactor, then reacted at 140 °C in a forced air drying oven for 4 h, centrifuged to obtain the precipitate, washed with water, and dried to obtain Ni2P QDs.
[0086] Example 3 Preparation of CoP QDs In the glove box, take 20 ml of the BPQDs supernatant after centrifugation at 9000 rpm, add 10 mg of sodium methoxide, pH 10.4, 270 mg of Co(NO3)2⋅6H2O, and stir to obtain a uniform dispersion. The dispersion was transferred to a polytetrafluoroethylene (25 ml) reactor, then reacted at 150 °C in a forced air drying oven for 5 h, centrifuged to obtain the precipitate, washed with water, and dried to obtain CoP QDs.
[0087] Example 4 Preparation of Fe3P QDs In the glove box, take 20 ml of the BPQDs supernatant after centrifugation at 9000 rpm, add 10 mg of potassium ethoxide, pH 10.3, 300 mg of FePO4, and stir to obtain a uniform dispersion. The dispersion was transferred to a polytetrafluoroethylene (25 ml) reactor, then reacted at 160 ° C in a forced air drying oven for 6 h, centrifuged to obtain the precipitate, washed with water, and dried to obtain Fe3P QDs.
[0088] Example 5 Preparation of Cu3P QDs In the glove box, take 20 ml of the BPQDs supernatant after centrifugation at 9000 rpm, add 10 mg of sodium ethoxide, pH 10.3, 300 mg of CuSO4, and stir to obtain a uniform dispersion. The dispersion was transferred to a polytetrafluoroethylene (25 ml) reactor, then reacted at 180 ° C in a forced air drying oven for 8 h, centrifuged to obtain the precipitate, washed with water, and dried to obtain Cu3P QDs.
[0089] Example 6 Characterization of TMP QDs TEM test TEM images were obtained on a Tecnai G2 F20 S-Twin transmission electron microscope at an accelerating voltage of 200 kV. The samples were dispersed in EtOH or ultrapure water, and 5 μl was dropped onto an ultrathin carbon support film carrier for observation. The average particle sizes of the TMP QDs obtained in Examples 2-5 were 2.0 nm for Ni2P QDs, 3.4 nm for CoP QDs, 4.1 nm for Fe3P QDs, and 5.0 nm for Cu3P QDs. Figure 1 Transmission electron microscope images of Ni2P QDs, CoP QDs, Fe3P QDs, and Cu3P QDs.
[0090] DLS Test The samples of Examples 2-5 were dispersed in water and directly tested on a dynamic light scattering nanoparticle size instrument. The DLS particle sizes of Ni2P QDs, CoP QDs, Fe3P QDs, and Cu3P QDs measured in Examples 2-5 were 2.0±0.2 nm, 3.4±0.3 nm, 4.1±0.3 nm, and 5.0±0.2 nm, respectively, and the results were consistent with the TEM results.
[0091] XRD test XRD patterns were obtained from a Rigaku SmartLab diffractometer (40 kV, 30 mA). The powder samples were filled into the grooves of silicon wafers for testing. All patterns corresponded to the standard cards, proving the successful preparation of TMP QDs obtained in Examples 2-5. Figure 2 XRD patterns of Ni2P QDs, CoP QDs, Fe3P QDs, Cu3P QDs and BPQDs.
[0092] When the black phosphorus crystal transformation material is Ni2P QDs, X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 40.8°, 44.6°, 47.3°, and 54.2°; When the black phosphorus crystal transformation material is CoP QDs, X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 31.6°, 46.2°, and 58.1°; When the black phosphorus crystal transformation material is Fe3P QDs, X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 41.4°, 41.8°, 42.2°, 43.1°, and 45.3°; When the black phosphorus crystal transformation material is Cu3P QDs, X-ray powder diffraction has characteristic peaks at 2-Theta of approximately 36.0°, 39.1°, 41.6°, 45.2°, 46.3°, and 47.4°.
[0093] XPS Test XPS spectra were obtained from a Thermo Escalab 250Xi spectrometer (Waltham, MA, USA) equipped with an X-ray source (Al Kα 1486.6 eV). XPS spectra were used to analyze the surface elements of the materials. The sample preparation method was to disperse the sample in EtOH and then drop it onto a Si wafer and dry it for analysis. Taking Cu3P QDs as an example, Figure 3 The XPS spectra of Cu3PQDs are shown in Figure 2. The XPS spectra of P 2p and Cu 2p regions both show two spin-orbit double peaks, proving that they are Cu3P structures.
[0094] EDS Testing The EDS test method is the same as TEM, and the sample elements can be analyzed. The TMP QDs obtained in Examples 2-5 can all correspond to the EDS spectra. Taking Ni2P QDs as an example, Figure 4 EDS spectra of Ni2P QDs and BPQDs. In addition to the carbon adsorbed on the surface, Ni2P QDs show a molar ratio of nickel and phosphorus (Ni:P) ≈ 2:1, but only phosphorus is observed in BPQDs.
[0095] In CoP QDs quantum dots, the molar ratio of cobalt and phosphorus elements (Co:P) is ≈2:1; in Fe3P QDs quantum dots, the molar ratio of iron and phosphorus elements (Fe:P) is ≈2:1; in Cu3P QDs quantum dots, the molar ratio of copper and phosphorus elements (Cu:P) is ≈2:1.
[0096] Example 7 Photothermal conversion performance test of TMP QDs UV-Vis absorption spectrum of TMP QDs The TMP QDs (i.e., Ni2P QDs, CoP QDs, Cu3P QDs, Fe3P QDs) obtained in Examples 2-5 were dispersed in water, placed in a 2 ml quartz dish, and tested by a UV-visible spectrophotometer (Lambda 25, PerkinElmer, USA). The absorption of TMP QDs at 1064 nm was concentration-dependent. Figure 5 Only the absorption curves of Fe3P QDs at different concentrations are shown. Compared with BPQDs, the absorption of TMP QDs at the same concentration is greatly enhanced. Table 1 shows the absorption of BPQDs and TMPQDs at 1064 nm at concentrations of 50 ppm and 100 ppm.
[0097] Table 1: Absorption of BPQDs and TMP QDs at 1064 nm (50 ppm, 100 ppm) .
[0099] Extinction coefficient test The extinction coefficient was calculated by the following equation: A = εbc. A is the absorbance of TMP QDs at 1064 nm, b is the diameter of the quartz cuvette (1 cm), and c is the concentration of TMP QDs. Compared with BPQDs, the extinction coefficients of TMP QDs are improved. Table 2 shows the extinction coefficients of BPQDs and TMP QDs.
[0100] Table 2: Extinction coefficients of BPQDs and TMP QDs .
[0102] Photothermal heating curve test TMP QDs were dispersed in PBS solution and a continuous fiber-coupled semiconductor diode laser was used as a near-infrared light source (1064 nm, 1.0 W / cm 2 ) irradiation, the temperature change is monitored by an infrared thermal imaging camera. The temperature change is recorded and the heating curve is plotted. When the concentration of TMP QDs reaches 100 ppm, the temperature can rise to 48.2-53.4 o C. However, 100 ppm of BPQDs can only be heated to 40.9 o C. TMP QDs exhibit a photothermal effect that depends on laser power (0.3, 0.5, 0.75, 1.0 W / cm 2 ), with the increase of laser power density, the temperature rise will also increase (Table 3).
[0103] Table 3: Temperature changes of BPQDs and TMP QDs
[0104] Photothermal stability To further evaluate the photothermal stability of TMP QDs in the NIR-II window, 1064 nm laser irradiation was performed for 2 minutes (laser on), followed by natural cooling to room temperature (laser off), and five on / off cycles were performed and the cyclic temperature changes were recorded. No obvious degradation of the photothermal performance was observed during the cycle, confirming the photothermal stability of TMP QDs.
[0105] Photothermal conversion efficiency Photothermal conversion efficiency ( ) is calculated by the following formula: (1). Where Aλ is the absorbance of NiP@Lipo and I is the laser power density.
[0106] Q Dis This can be determined by (2) Where m D is the mass of aqueous solution, c D is the specific heat capacity of the aqueous solution, ΔT is the temperature change of the aqueous solution under the action of laser, and t is the irradiation time.
[0107] In formula (I), only hA is unknown, which can be determined by the following equation: (3); (4); t = - τ (ln θ) (5).
[0108] NIR-II photothermal conversion efficiency of TMP QDs ( ) is 43.5-48.6%, which is much higher than the photothermal conversion efficiency of BPQDs ( ).
[0109] Example 8 Construction of liposome composite 1 (Ni2P@Lipo) 1 mol of dipalmitoylphosphatidylcholine (DPPC), 0.5 mol of cholesterol, 0.4 mol of cRGD and 0.2 mol of Ni2P QDs were dissolved in 10 ml of CHCl3 and dried under reduced pressure by rotary evaporator at 37°C to form a film. The lipid film was hydrated with PBS solution (pH = 7.4) and sonicated with a VCX 130 probe sonicator. The probe sonication time was 10 min (20 seconds on and 10 seconds off in each cycle). The temperature was controlled with the help of an ice water bath. After the sonication, the film was centrifuged at 5000 rpm for 10 min and the supernatant was retained for later use.
[0110] Construction of liposome composite 2 (Cu3P@Lipo) 1 mol of dipalmitoylphosphatidylcholine (DPPC), 0.6 mol of cholesterol, 0.5 mol of cRGD and 0.3 mol of Cu3P QDs were dissolved in 10 ml of CHCl3 and dried under reduced pressure by rotary evaporator at 37°C to form a film. The lipid film was hydrated with PBS solution (pH = 7.4) and sonicated with a VCX 130 probe sonicator. The probe sonication time was 15 min (30 seconds on and 10 seconds off in each cycle). The temperature was controlled with the help of an ice water bath. After the sonication, the film was centrifuged at 5000 rpm for 10 min and the supernatant was kept for later use.
[0111] Construction of liposome composite 3 (CoP@Lipo) 1 mol of dipalmitoylphosphatidylcholine (DPPC), 0.7 mol of cholesterol, 0.7 mol of cRGD and 0.4 mol of CoP QDs were dissolved in 10 ml of CHCl3 and dried under reduced pressure by rotary evaporator at 37°C to form a film. The lipid film was hydrated with PBS solution (pH= 7.4) and sonicated with a VCX 130 probe sonicator. The probe sonication time was 20 min (40 s on and 10 s off in each cycle). The temperature was controlled with the help of an ice water bath. After sonication, the film was centrifuged at 5000 rpm for 10 min and the supernatant was retained for later use.
[0112] Construction of liposome composite 2 (Fe3P@Lipo) 1 mol of dipalmitoylphosphatidylcholine (DPPC), 0.6 mol of cholesterol, 0.5 mol of cRGD and 0.3 mol of Fe3P QDs were dissolved in 10 ml of CHCl3 and dried under reduced pressure by rotary evaporator at 37°C to form a film. The lipid film was hydrated with PBS solution (pH = 7.4) and sonicated with a VCX 130 probe sonicator. The probe sonication time was 15 min (30 seconds on and 10 seconds off in each cycle). The temperature was controlled with the help of an ice water bath. After sonication, the film was centrifuged at 5000 rpm for 10 min and the supernatant was retained for later use.
[0113] Example 9 Characterization of liposome composites 1-3 Through TEM and DLS tests, the diameter of liposome composites 1-3 (Ni2P@Lipo, Cu3P@Lipo, CoP@Lipo, Fe3P@Lipo) was measured to be 70-140 nm. Figure 6 , Figure 7 They are TEM and DLS images of the liposome materials obtained from Ni2P@Lipo and Cu3P@Lipo in Example 8. The particle size of Ni2P@Lipo is about 110 nm, the particle size of CoP@Lipo is about 90 nm, and the particle size of Fe3P@Lipo is about 120 nm.
[0114] Example 10 Anti-tumor drug encapsulation 1 (Ni2P-cyclophosphamide@Lipo) The liposome composite material 1 (Ni2P@Lipo) was dispersed in a citric acid / sodium citrate dispersion at pH 3.0, and citric acid was added in a gradient to further adjust the pH to 6.0, and an excess of cyclophosphamide was added. The unencapsulated cyclophosphamide was separated using a Sephadex G-50 column and eluted with PBS (pH 7.4) as the eluent.
[0115] Coating of anti-tumor drugs 2 (Cu3P-oxaliplatin@Lipo) Liposome composite 2 (Cu3P@Lipo) was dispersed in a citric acid / sodium citrate dispersion at pH 4.0, and citric acid was added in a gradient to further adjust the pH to 7.0, and excess oxaliplatin was added. Unencapsulated oxaliplatin was separated using a Sephadex G-50 column and eluted with PBS (pH 7.4) as the eluent.
[0116] Coating of anti-tumor drugs 3 (CoP-doxorubicin@Lipo) Liposome composite 3 (CoP@Lipo) was dispersed in citric acid / sodium citrate dispersion, pH = 5.0, and citric acid was added in a gradient to further adjust the pH to 8.0, and excess doxorubicin was added. Unencapsulated doxorubicin was separated using a Sephadex G-50 column and eluted with PBS (pH = 7.4) as the eluent.
[0117] Coating of anti-tumor drugs 2 (Fe3P-oxaliplatin@Lipo) The liposome composite material 2 (Fe3P@Lipo) was dispersed in a citric acid / sodium citrate dispersion at pH 4.0, and the pH was further adjusted to 7.0 by gradient addition of citric acid, and an excess of oxaliplatin was added. The unencapsulated oxaliplatin was separated using a Sephadex G-50 column and eluted with PBS (pH 7.4) as the eluent.
[0118] Embodiment 11 Encapsulation efficiency of liposome composites The coverage rate was measured by fluorescence spectrophotometry (λ ex =505 nm, λ em=559 nm) test. Calculated according to the following equation: Coverage = (I max -I0) / I max *100%, where I0 is the fluorescence intensity of the liposome suspension at the initial stage, I max is the fluorescence intensity after adding 0.5% Triton X-100. The encapsulation rate of the anti-tumor drug in Example 9 is 94-98%. Table 4 shows the encapsulation rate of different anti-tumor drugs by liposome composite materials 1-3.
[0119] Table 4 Antitumor drug encapsulation rate of liposome composites
[0120] In addition to the coating rate test for the preparation method of Example 10, the data in Table 4 above also tested the coating of other cases in the fixed coating case of Example 10, where the coating method was the same as that of Example 10.
[0121] Example 12 Drug release efficiency In Example 10, the liposome composite material 1 (Ni2P-cyclophosphamide@Lipo) was coated with cyclophosphamide, and the anti-tumor drug was rapidly released and separated from the liposome under 1064 nm light irradiation. The release curve showed a sudden release within the first 5 minutes, and the release efficiency was between 30.6% and 48.8%. The release of the anti-tumor drug stopped when the NIR-II light was turned off, and the release of the anti-tumor drug was restarted when the NIR-II light was restored.
[0122] Example 13 Stability test The liposome composite material 2 (Cu3P-oxaliplatin@Lipo) was dispersed in PBS solution (pH=7.4) and optical images were collected after 0, 1, 2, and 3 weeks. The liposome composite material did not degrade after 3 weeks, indicating the stability of the liposome composite material.
[0123] Embodiment 14 Cell culture MCF-7 cell line was purchased from China Center for Type Culture Collection (CTCC). The cells were added to DMEM medium containing 10% (v / v) fetal bovine serum (FBS) and cultured in a cell culture incubator at 37°C and 5% CO2.
[0124] Embodiment 15 Cytotoxicity of liposome composites The cells were seeded in 96-well plates at a density of 5 × 10 4The cells were cultured at a density of 100 ppm / ml for 24 hours. The original culture medium was replaced with a culture medium containing serially diluted liposome composites (Ni2P-cyclophosphamide@Lipo) and the final concentration was adjusted to 20, 40, 60, 80 and 100 ppm. After 24 hours of culture, the culture medium was removed and a culture medium containing 10% (v / v) CCK-8 solution was added to each well, followed by incubation for 2 hours, and the absorbance at 450 nm was measured on a microplate reader. Untreated cells served as the control group. After culturing for 48 hours with the addition of 100 ppm concentration of liposome composites, the survival rate of MCF-7 cells was close to 100%, indicating that the liposome composites had low cytotoxicity and good biocompatibility. Figure 8 Cell survival rate under culture with different concentrations of liposome composite materials.
[0125] Example 16 Intracellular uptake of liposome composites Fluorescence images of intracellular uptake of liposome composites were observed by confocal laser scanning microscopy. The specific method is as follows: Cy5.5-labeled liposome composites were prepared by adding 0.1 mg / ml Cy5.5 to the liposome composite dispersion (Ni2P-cyclophosphamide@Lipo in PBS) and stirring at room temperature for 4 hours in the dark. Excess dye molecules were removed by centrifugation and washed with water for more than 5 times until no fluorescent signal was detected in the supernatant. MCF-7 cells were seeded in confocal culture dishes (5×10 4 ) and added 10% (v / v) FBS in DMEM medium and cultured overnight at 37 °C, 5% CO2. The cells were mixed with the medium containing Cy5.5-labeled liposome composites (2μg / ml), sampled at different time intervals (2, 4, 8 and 12 hours), and washed twice with PBS. Then, the cells were fixed with 4% paraformaldehyde (PFA) and stained with 4′,6-diamidino-2-phenylindole (DAPI) and observed continuously for 10 minutes on a confocal laser scanning microscope at a concentration of 100 ng / ml. After incubation for 2 hours, the liposome composites achieved effective and rapid intracellular uptake, as shown in Figure 2. Fig. 9 shown.
[0126] Embodiment 17 In vitro anti-tumor assay MCF-7 cells were seeded in 96-well plates and cultured for 24 h at a density of 5 × 10 4The cells were divided into four groups for the experiment, namely the control group (pure PBS solution), the photothermal group (Ni2P@Lipo), the chemotherapy group (Ni2P-cyclophosphamide@Lipo), and the photothermal-chemotherapy group (Ni2P-cyclophosphamide@Lipo). The concentration of the materials in the latter three groups was the same (100 ppm). After culturing the MCF-7 cells with the four groups of materials for 4 hours, the cells in the photothermal group and the photothermal-chemotherapy group were illuminated with a 1064 nm laser (1.0 W / cm 2 ) After 10 minutes of irradiation, the cells were cultured for 24 hours. The cell viability of each group was determined by CCK-8 kit. In the live / dead staining experiment, the culture medium was removed and calcein AM (5 μg / ml) and propidium iodide PI (5 μg / ml) were added. After 15 minutes of culture, the cells were washed with PBS and the fluorescent images of the treated tumor cells were obtained by fluorescence microscopy. The cell survival rates of the chemotherapy group, photothermal group, and photothermal-chemotherapy group were 50-61%, 40-51%, and 0-3%, respectively. Fig.10 The figure shows the cell survival rate of the four treatment groups.
[0127] Embodiment 18 Animal and xenograft tumor models Balb / c nude mice (female, 18–20 g, 4–6 weeks old) were purchased from Charles River Laboratory Animal Technology Co., Ltd. (Beijing, China) and maintained in a laminar flow cabinet under specific pathogen-free conditions (18–22 o C, relative humidity 50-70%, 12 h dark cycle). The animals had free access to tap water and standard pelleted food. All animal experiments were performed in accordance with the Institute's Guide for the Care and Use of Laboratory Animals. The animal experimental protocol was approved by the Administrative Department of the Animal Research Committee of the Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences. During the tumor xenograft model, approximately 1 × 10 7 The cells were injected subcutaneously into the posterior right leg of the mice. The tumor size was measured with a vernier caliper and the tumor volume was calculated according to the formula: Volume (V) = (tumor length) x (tumor width) 2 / 2.
[0128] Embodiment 19 In vivo distribution studies After a single intravenous injection of Cy5.5-labeled liposome composite (Ni2P-cyclophosphamide@Lipo) (2.5 mg / kg per tumor-bearing mouse), the mice were imaged and the fluorescence intensity was quantified using the small animal in vivo optical three-dimensional imaging system (IVIS) at 6, 12, 24, 48 and 96 hours after injection. After the imaging was completed, the mice were killed and the heart, liver, spleen, lung, kidney, and tumor were immediately collected for ex vivo fluorescence imaging. Unlike the fluorescence signal of free TMP QDs distributed throughout the mouse body, the fluorescence signal of the liposome composite was targeted and concentrated at the tumor site, such as Fig.11 shown.
[0129] Embodiment 20 Photothermal effect testing of tumor sites 24 hours after injection of the liposome composite (Ni2P-cyclophosphamide@Lipo), the mice were anesthetized and illuminated with a 1064 nm near-infrared laser (1.0 W / cm 2 ) for 5 minutes. Infrared thermal imaging photos were obtained by an infrared thermal imager, and the tumor temperature was monitored by an imaging camera. The tumor temperature of mice treated with liposome composites rose rapidly and steadily to 58.5-63.4℃ after 10 minutes of 1064 nm laser irradiation.
[0130] Embodiment 21 In vivo photothermal synergistic chemotherapy anti-tumor experiment When the tumor volume of MCF-7 xenografts reached approximately 150 mm 3 At the same time, the mice were randomly divided into 4 groups, each containing 5 mice. One group (control group) was intravenously injected with PBS, and the other groups (treatment groups: chemotherapy group ((Ni2P@Lipo injection)), photothermal group (Ni2P-cyclophosphamide@Lipo injection), photothermal-chemotherapy group ((Ni2P-cyclophosphamide@Lipo injection)) were intravenously injected with liposome composites (2.5 mg / kg). 24 hours after the injection, the mice in the photothermal group and photothermal-chemotherapy group were anesthetized, and the entire tumor area was illuminated with a 1064 nm near-infrared laser (1.0 W / cm 2 ) for 10 min. The other two groups of mice were treated without NIR irradiation. Tumor volume and body weight were recorded every 2 days. On day 14, all mice were sacrificed for anatomical and histopathological analysis. The anti-tumor effect of mice treated with single photothermal therapy or chemotherapy was improved, but the tumor could not be completely ablated and recurred. The tumor of mice treated with photothermal-chemotherapy combination was completely ablated, such as Fig.12 shown.
[0131] Embodiment 22 Histopathology and TUNEL analysis After the treatment, the heart, liver, spleen, lung, and kidney of the mice were embedded in paraffin. The sections were cut into 5 μm thick sections and stained with H&E. The sections were observed under a light microscope. According to the manufacturer's requirements, the tumor tissue was stained with TUNEL and detected using the in situ death POD kit on paraffin-embedded in situ tumor sections. DAPI counterstaining was used to quantify cells with intact nuclei, and MCF-7 apoptotic cells labeled with fluorescein dye were examined by fluorescence microscopy. The weight of the mice did not change during the treatment, and there was no damage to the organs, indicating the biological safety of this treatment. Compared with other groups, the tumor tissues of mice in the photothermal chemotherapy group showed more severe nuclear atrophy and apoptosis, such as Fig.13 shown.
Claims
1. A black phosphorus crystal transformation material, characterized in that: The black phosphorus crystal transformation material is transition metal phosphide quantum dots formed by black phosphorus crystals and transition metal ions, and the average particle size of the composite material is 2.0-10.0 nm.
2. The black phosphorus crystal transformation material according to claim 1, characterized in that: The transition metal ions include Ni 2+ 、Co 2+ , Fe 3+ , Cu 2+ One or more of .
3. The black phosphorus crystal transformation material according to claim 2, characterized in that: The transition metal phosphide quantum dots include any one of nickel phosphide quantum dots Ni2P QDs, cobalt phosphide quantum dots Ni2P QDs, iron phosphide quantum dots Ni2P QDs, and copper phosphide quantum dots Ni2P QDs; The black phosphorus crystal transformation material is Ni2P QDs, and the 2-Theta of X-ray powder diffraction has characteristic peaks at about 40.8°, 44.6°, 47.3°, and 54.2°; The black phosphorus crystal transformation material is CoP QDs, and the 2-Theta of X-ray powder diffraction has characteristic peaks at about 31.6°, 46.2°, and 58.1°; The black phosphorus crystal transformation material is Fe3P QDs, and the 2-Theta of X-ray powder diffraction has characteristic peaks at about 41.4°, 41.8°, 42.2°, 43.1°, and 45.3°; The black phosphorus crystal transformation material is Cu3P QDs, and the 2-Theta of X-ray powder diffraction has characteristic peaks at about 36.0°, 39.1°, 41.6°, 45.2°, 46.3°, and 47.4°; The average particle size of the composite material is 2.0-10.0 nm.
4. The method for preparing the black phosphorus crystal transformation material according to any one of claims 1 to 3, characterized in that: The black phosphorus crystal transformation material is a transition metal salt that undergoes a solvothermal reaction with black phosphorus crystals BPQDs in a strong alkaline environment to obtain transition metal phosphide quantum dots TMP QDs, which is the black phosphorus crystal transformation material.
5. The method for preparing the black phosphorus crystal transformation material according to claim 4, characterized in that: The strongly alkaline environment refers to an environment with a pH of 9-13.
6. The method for preparing the black phosphorus crystal transformation material according to claim 5, characterized in that: The strong base used in the strong alkaline environment includes any one of potassium methoxide, sodium methoxide, potassium ethoxide and sodium ethoxide.
7. The method for preparing the black phosphorus crystal transformation material according to claim 6, characterized in that: The transition metal salt is a transition metal ion including Ni 2+ 、Co 2+ , Fe 3+ , Cu 2+ One or more chlorides, nitrates, phosphates, and sulfates.
8. The method for preparing the black phosphorus crystal transformation material according to claim 4, characterized in that: The hydrothermal reaction temperature is 140-180°C, the reaction time is 4-8h, and the hydrothermal reaction process is in an oxygen-free environment; The solvent is one or more of N-methylpyrrolidone and N,N-dimethylformamide.
9. A photothermal effect material, characterized in that: The invention comprises the black phosphorus crystal transformation material according to any one of claims 1 to 3 or the transition metal phosphide quantum dots prepared by the method according to any one of claims 4 to 7.
10. The photothermal effect material according to claim 9, characterized in that: The transition metal phosphide quantum dots are applied to materials that achieve light-to-heat conversion performance under a light source of 1000-1500nm.
11. Use of a material containing transition metal phosphide quantum dots in the preparation of a drug for targeted drug delivery to achieve anti-tumor effects, characterized in that: The transition metal phosphide quantum dots include the transition metal phosphide quantum dots described in any one of claims 1 to 3 or the transition metal phosphide quantum dots prepared by the method described in any one of claims 4 to 7.
12. Use of a material comprising transition metal phosphide quantum dots in the preparation of a drug for targeted delivery to achieve tumor clearance, characterized in that: The transition metal phosphide quantum dots include the black phosphorus crystal change material described in any one of claims 1 to 3 or the black phosphorus crystal change material prepared by the method described in any one of claims 4 to 7.
13. A liposome nanoplatform, characterized in that: The invention comprises liposomes and the transition metal phosphide quantum dots according to any one of claims 1 to 3 or the transition metal phosphide quantum dots prepared by the method according to any one of claims 4 to 7.
14. The liposome nanoplatform according to claim 13, characterized in that: The liposome nano-platform is prepared by dissolving dipalmitoylphosphatidylcholine, cholesterol, cRGD and transition metal phosphide quantum dots in a solvent, drying under reduced pressure by a rotary evaporator to generate a lipid membrane; performing a hydration reaction on the lipid membrane with a PBS solution, performing sonication treatment and centrifugation on the hydrated lipid membrane, and retaining the supernatant to obtain the liposome nano-platform.
15. An anti-tumor drug, characterized in that: The anti-tumor drug comprises an anti-tumor drug active ingredient and transition metal phosphide quantum dots.
16. The anti-tumor drug according to claim 15, characterized in that: The anti-tumor drug is a composite drug formed by encapsulating the active ingredients of the anti-tumor drug and transition metal phosphide quantum dots into the lipid bilayer and inner layer of the liposome.
17. The anti-tumor drug according to claim 16, characterized in that: The anti-tumor drug is prepared by dispersing the liposome nano-platform in a citric acid / sodium citrate dispersion at pH 3.0-5.0, further adjusting the pH to 6.0-8.0 by adding citric acid, and then adding the active ingredient of the anti-tumor drug to achieve the encapsulation of the anti-tumor drug, thereby obtaining the anti-tumor drug.
18. The anti-tumor drug according to claim 17, characterized in that: The active ingredients of the anti-tumor drug include one or more of alkylating drugs, platinum drugs, and anthracycline drugs; The alkylating agent drugs include nitrogen mustard or cyclophosphamide; the platinum drugs include cisplatin or oxaliplatin; and the anthracycline drugs include doxorubicin.
19. The anti-tumor drug according to any one of claims 15 to 18, characterized in that: The anti-tumor drug can be quickly released under light irradiation and separated from the liposome to be used in preparing drugs for treating tumors.
20. The anti-tumor drug according to claim 19, characterized in that: The light irradiation is irradiation under a light source of 1000-1500 nm; the dosage of the anti-tumor drug is 25-100 ppm.
21. An optically switchable anti-tumor drug, characterized in that: The invention comprises the anti-tumor drug according to any one of claims 15 to 18.
22. The anti-tumor drug according to any one of claims 15 to 20 or the optically switched anti-tumor drug according to claim 21, characterized in that: The cells of tumor diseases include MCF-7 cells, Hela cells, 4T1 cells or MIA PaCa-2 cells.
Citation Information
Patent Citations
Black phosphorus quantum dot and preparation method thereof
CN106190120A